Low inflation in the euro area: Causes and consequences - Matteo Ciccarelli; Chiara Osbat (European Central Bank (ECB), 2017)
After 2012, inflation has been unexpectedly low across much of the developed world and economists speak of a “missing inflation” puzzle, namely inflation was expected to be higher on the back of an ongoing recovery. This paper investigates the causes and consequences of low inflation in the euro area after 2012 and analyses whether monetary policy has been successful in dampening the risks associated to low inflation. The paper finds that the missing inflation was primarily due to cyclical factors – domestic in the earlier part of the period and global in the latter part – and that the Phillips curve remains a useful tool in understanding inflation dynamics over the period of interest. The succession of negative shocks constrained headline inflation for a prolonged period, and there is evidence of an increase in the persistence of inflation and a fall in the trend inflation rate, which had begun to have a greater influence on longer-term inflation expectations. This may have signalled uncertainty over the effectiveness of unconventional monetary policy measures, but public belief in the ECB's commitment to keep the annual rate of HICP inflation below but close to 2% has remained intact. The paper concludes that unconventional monetary policy measures are effective in mitigating the downside risks to price stability, curtailing risks of de-anchoring, and expanding aggregate demand.
Keywords: E31; E52; E58; 330; inflation expectations; low inflation; Phillips curve; unconventional monetary policy